Polishing solution for improving edge roughness

By introducing alkali metal hydroxide, quaternary ammonium hydroxide and sol-type silica into the polishing liquid, combining with surfactant, adjusting the pH value, the problem of low polishing rate is solved and efficient polishing is achieved Reduced results and costs.

CN119193006APending Publication Date: 2024-12-27JIANGSU SHANSHUI SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411465118.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing polishing liquid is used for wafer edge polishing with low polishing rate, which cannot meet the high requirements of high-end semiconductor devices for flatness and finish.

Method used

A polishing liquid that improves edge roughness, including alkali metal hydroxide, quaternary ammonium hydroxide, amine and other rate accelerators, combined with sol-type silica and surfactant, adjusts the pH between 9-12 , improve polishing rate and surface quality through synergistic action.

Benefits of technology

It significantly improves the silicon removal rate, reduces the amount of abrasive used in the polishing liquid, reduces the cost, and improves the polishing efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193006A_ABST
    Figure CN119193006A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical mechanical polishing, in particular to a polishing solution for improving edge roughness, which comprises the following components in parts by weight: 10-80 parts of sol-type silicon dioxide; 0.05 to 8 parts of a rate accelerator; 0.01 to 0.5 part of a surfactant; 0.04 to 0.45 part of a pH (Potential of Hydrogen) regulator; 15 to 25 parts of water; the rate accelerator is selected from at least one of alkali metal hydroxide, alkali metal carbonate, quaternary ammonium hydroxide and amine. By introducing the rate accelerator, the invention provides the chemical mechanical polishing solution which is high in alkali content, high in silicon removal rate and capable of protecting edges from being stained; and meanwhile, by introducing the rate accelerator, a relatively high silicon removal rate is obtained, so that the use amount of the grinding material in the polishing solution is reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical mechanical polishing, and in particular to a polishing liquid for improving edge roughness. Background Art

[0002] With the continuous advancement of semiconductor technology and the expansion of the market size, the demand for chemical mechanical (CMP) polishing liquid, as a key material in the semiconductor manufacturing process, continues to grow. In particular, driven by the continued growth in demand for electronic products such as smartphones, computers, and IoT devices, as well as the development of emerging technologies such as 5G and artificial intelligence, the demand for semiconductor chips continues to increase, thereby driving the growth of the CMP polishing liquid market. In the manufacture of high-end semiconductor devices and circuits, higher requirements are placed on the flatness and smoothness of the wafer surface. Edge polishing technology can meet the needs of these high-end applications and improve product performance and reliability.

[0003] Edge polishing can effectively remove the rough part of the wafer edge through the dual effects of mechanical grinding and chemical etching, making the wafer surface smoother. This smooth surface is not only conducive to the subsequent process, but also improves the yield and reliability of the chip. During the manufacturing process of the wafer, the edge part is often prone to mechanical damage, cracks and other defects. Edge polishing can remove these defects, reduce the risk of wafer breakage in subsequent processing, and improve the overall quality.

[0004] Wafer edge polishing liquid effectively removes rough parts and tiny defects on the edge of the wafer, such as mechanical damage and cracks, through the synergistic effect of chemical corrosion and mechanical friction, making the edge of the wafer smoother. The abrasive particles and chemical components in the polishing liquid can penetrate into the microstructure of the wafer edge, remove surface unevenness and tiny defects, and improve the overall quality of the wafer. The mechanical strength of the polished wafer edge is improved, making it tougher and able to withstand greater external impact without breaking easily. In summary, chemical mechanical polishing has multiple functions in the semiconductor manufacturing process. It can not only improve the quality and performance of the wafer edge, but also optimize the manufacturing process, improve production efficiency, and meet the needs of high-end applications. Therefore, in the wafer manufacturing process, it is crucial to select a suitable edge polishing liquid and optimize the polishing process.

[0005] When the existing polishing liquid is used for polishing the edge of a wafer, there is a problem of low polishing rate. Summary of the invention

[0006] The object of the present invention is to provide a polishing liquid for improving edge roughness, and to increase the polishing rate through the synergistic effect of various components.

[0007] The technical solution adopted by the present invention to solve its technical problem is:

[0008] A polishing liquid for improving edge roughness, comprising the following components in parts by weight:

[0009]

[0010] The rate accelerator is selected from at least one of alkali metal hydroxides, alkali metal carbonates, quaternary ammonium hydroxides, and amines.

[0011] Optionally, the rate accelerator is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, tetramethylammonium hydroxide, triethanolamine, ammonia water, benzalkonium chloride, benzalkonium bromide, bis-decyl dimethyl ammonium chloride, laurylamine dipropylene diamine, propylene diamine, quaternary ammonium oxide, alkyl dimethyl benzyl ammonium chloride, complex quaternary ammonium salt and polyquaternary ammonium salt.

[0012] Optionally, the particle size of the sol-type silica is in the range of 30-150 nm.

[0013] Optionally, the surfactant is selected from at least one of a nonionic surfactant, an amphoteric surfactant, and a polyol surfactant.

[0014] Optionally, the surfactant is selected from at least one of long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylamide and polyethers.

[0015] Optionally, 0.01-1 part of a dispersant is also included.

[0016] Optionally, the dispersant is an inorganic electrolyte dispersant; the inorganic electrolyte dispersant is selected from at least one of phosphates, silicates and carbonates.

[0017] Optionally, the pH adjuster is an organic acid.

[0018] Optionally, the pH adjuster is selected from at least one of formic acid, acetic acid, propionic acid, citric acid, oxalic acid, tartaric acid, malic acid, lactic acid, nitrilotriacetate amine, sodium nitrilotriacetate, ethylenediaminetetraacetic acid, and sodium ethylenediaminetetraacetate.

[0019] Optionally, the pH value of the polishing liquid for improving edge roughness is in the range of 9-12.

[0020] The beneficial effects of the present invention are:

[0021] The present application provides a chemical mechanical polishing liquid with high alkali content, high silicon removal rate and the ability to protect edges from contamination by introducing a rate accelerator; at the same time, by introducing the rate accelerator, a higher silicon removal rate is obtained, thereby reducing the amount of abrasive used in the polishing liquid, which in turn helps to reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0023] Figure 1 is a microscope image of the edge of the silicon wafer after polishing in Example 1 of the present invention;

[0024] Figure 2 is a microscope image of the edge of a silicon wafer after polishing in Example 2 of the present invention;

[0025] Figure 3 is a microscope image of the edge of a silicon wafer after polishing in Example 3 of the present invention;

[0026] Figure 4 is a microscope image of the edge of a silicon wafer after polishing in Example 3 of the present invention;

[0027] Figure 5 is a comparison chart of removal rates when the polishing liquids in Examples 1-4 of the present invention are used to polish silicon wafers;

[0028] Figure 6 It is a comparison chart of the static corrosion results of the polishing liquid on the silicon wafer in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0030] In order to solve the problem that the existing polishing liquid has a low polishing rate when used for wafer edge polishing, the present application provides a polishing liquid for improving edge roughness. The polishing liquid comprises the following components in parts by weight:

[0031]

[0032] The rate accelerator refers to a substance that can increase the silicon polishing rate, and preferably the rate accelerator is selected from at least one of alkali metal hydroxides, alkali metal carbonates, quaternary ammonium hydroxides, and amines.

[0033] Rate accelerators refer to substances that can increase the polishing rate of silicon. Polishing liquid rate accelerators involve using specific chemicals or formulas to increase the material removal rate during the polishing process while maintaining or improving the surface quality. Polishing liquid rate accelerators usually include a variety of chemical components that work synergistically in the polishing liquid to accelerate the chemical reaction and mechanical removal process on the material surface, thereby increasing the polishing rate. At the same time, they may also have the functions of adjusting the pH value of the polishing liquid, improving the dispersion of the polishing liquid, and reducing surface roughness.

[0034] Specifically, in the rate accelerator, alkali metal hydroxide can accelerate the oxidation reaction on the metal surface by virtue of its strong alkalinity, alkali metal carbonate can both adjust the pH and act as a buffer, quaternary ammonium hydroxide promotes the polishing reaction by virtue of its excellent solubility and stability, and amine promotes the dissolution of metal ions by complexation, thereby significantly improving the polishing rate and optimizing the polishing quality.

[0035] The present application provides a chemical mechanical polishing liquid with high alkali content, high silicon removal rate and the ability to protect edges from contamination by introducing a rate accelerator; at the same time, by introducing the rate accelerator, a higher silicon removal rate is obtained, thereby reducing the amount of abrasive used in the polishing liquid, which in turn helps to reduce costs.

[0036] Specifically, the preferred rate accelerator of the present application is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, tetramethylammonium hydroxide, triethanolamine, propylenediamine, ammonia water, benzalkonium chloride, benzalkonium bromide, bis-decyl dimethyl ammonium chloride, laurylamine dipropylene diamine, quaternary ammonium oxide, alkyl dimethyl benzyl ammonium chloride, complex quaternary ammonium salt and polyquaternary ammonium salt.

[0037] The present application preferably has a mass concentration of 20%-60% of colloidal silica particles in the sol-type silica, more preferably 20%-50%, and even more preferably 30%; the preferred particle size range of the sol-type silica is 30-150nm, and even more preferably 30-120nm.

[0038] The surfactant in the polishing liquid is intended to improve polishing efficiency, improve polishing surface quality, and reduce environmental pollution. The surfactant in the polishing liquid mainly plays the role of dispersing, wetting, and stabilizing, which can improve the performance of the polishing liquid and thus improve the polishing effect.

[0039] The preferred surfactant of the present application is selected from at least one of nonionic surfactants, amphoteric surfactants, and polyol surfactants; wherein nonionic surfactants do not dissociate into ions in water, and their molecules contain both hydrophilic groups and hydrophobic groups, but the hydrophilic groups are usually composed of polar groups containing oxygen atoms (such as hydroxyl groups, ether bonds, etc.). This type of surfactant has good stability and is not easily affected by strong electrolytes.

[0040] It is further preferred that the surfactant is at least one selected from the group consisting of long-chain fatty alcohol polyoxyethylene ether (AEO), alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylamide and polyethers.

[0041] The polishing liquid provided in the present application also includes 0.01-1 parts of a dispersant.

[0042] The dispersant is preferably an inorganic electrolyte dispersant, and more preferably the inorganic electrolyte dispersant is at least one selected from phosphates, silicates, and carbonates.

[0043] The polishing liquid provided in the present application is prepared by uniformly mixing the components and then adjusting the pH value using a pH adjuster. The selection of the pH adjuster needs to take into account factors such as the properties of the material to be polished, the requirements of the polishing process, and environmental protection requirements. The present application preferably uses an organic acid as the pH adjuster. It is further preferred that the pH adjuster is selected from at least one of formic acid, acetic acid, propionic acid, citric acid, oxalic acid, tartaric acid, malic acid, lactic acid, nitrilotriacetate ammonium, sodium nitrilotriacetate, ethylenediaminetetraacetic acid, and sodium ethylenediaminetetraacetate.

[0044] The present application preferably has a pH value range of 9-12 for the polishing liquid for improving edge roughness, and more preferably 10.5-12.

[0045] The polishing liquid provided in the present application is prepared by simply and evenly mixing the above components, and then adjusting the pH value to a suitable pH value using a pH adjuster.

[0046] The polishing liquid provided in this application has significant advantages in removal rate, surface roughness, surface particle control, etc. by virtue of its unique composition combination and excellent performance. The polishing liquid can not only improve polishing efficiency and quality, but also reduce production costs and environmental pollution, and has broad application prospects and market value.

[0047] The reagents used in the present invention are all commercially available.

[0048] The present invention also provides a chemical mechanical planarization method for removing silicon edges, comprising the following polishing steps:

[0049] First, a Zhiling 1280 polishing machine was used, the polishing pad was SUBA800 flat pad, the polishing pressure was 280kg, the polishing head / disc speed was 30 / 29rpm, the circulation flow was 3L / min. The polishing disk temperature was controlled at 30±5℃.

[0050] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0051] Example 1

[0052] Prepare 5L of silicon edge polishing liquid:

[0053] According to the weight percentage, 0.18 parts of potassium hydroxide, 5 parts of tetramethylammonium hydroxide, 0.43 parts of citric acid, and 0.09 parts of alkylphenol polyoxyethylene ether are dissolved in 22 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 72 parts of colloidal silicon dioxide with a particle size of 60nm and a concentration of 40% under stirring to obtain edge polishing liquid No. 1, whose pH is about 11.

[0054] First, take the prepared No. 1 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the polishing test results are shown in Table 1, and the results under the silicon wafer edge microscope are shown in Figure 1 .

[0055] Secondly, take the above-configured No. 1 edge polishing liquid and conduct a static corrosion experiment with a liquid dilution ratio of 1:15; the experimental temperature is 30°C, the experimental time is 24 hours, the experimental object: lightly doped B silicon wafer, the specific implementation operation is as follows: place the diluted liquid in a water bath and heat it to the experimental temperature, then place the experimental piece - lightly doped silicon wafer in the liquid for 24 hours, compare the change in the weight of the experimental piece before and after the experiment, and the static corrosion results are shown in Table 2.

[0056] Example 2

[0057] Prepare 5L of silicon edge polishing liquid:

[0058] According to the weight percentage, 0.18 parts of potassium hydroxide, 5 parts of tetramethylammonium hydroxide, 0.43 parts of citric acid, and 0.09 parts of alkylphenol polyoxyethylene ether are dissolved in 22 parts of DIW to prepare a premixed solution; then the premixed solution is added to 72 parts of colloidal silicon dioxide with a particle size of 80nm and a concentration of 40% under stirring to obtain a No. 2 edge polishing liquid with a pH of about 11.

[0059] First, take the prepared No. 2 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 1, and the results under the silicon wafer edge microscope are shown in Figure 2 .

[0060] Secondly, take the above-configured No. 2 edge polishing liquid and conduct a static corrosion experiment with a liquid dilution ratio of 1:15; the experimental temperature is 30°C, the experimental time is 24 hours, the experimental object: lightly doped B silicon wafer, the specific implementation operation is as follows: place the diluted liquid in a water bath and heat it to the experimental temperature, then place the experimental piece - lightly doped silicon wafer in the liquid for 24 hours, compare the change in the weight of the experimental piece before and after the experiment, and the static corrosion results are shown in Table 2.

[0061] Example 3

[0062] Prepare 5L of silicon edge polishing liquid:

[0063] According to the weight percentage, 0.18 parts of potassium hydroxide, 4 parts of hexamethylammonium hydroxide, 0.04 parts of tartaric acid, and 0.06 parts of fatty acid polyoxyethylene ester are dissolved in 23 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 72 parts of colloidal silicon dioxide with a particle size of 60nm and a concentration of 40% under stirring to obtain No. 3 edge polishing liquid, whose pH is about 11.

[0064] First, take the prepared No. 3 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the polishing results are shown in Table 1, and the results under the silicon wafer edge microscope are shown in Figure 3 .

[0065] Secondly, take the above-configured No. 3 edge polishing liquid and conduct a static corrosion experiment with a liquid dilution ratio of 1:15; the experimental temperature is 30°C, the experimental time is 24 hours, the experimental object: lightly doped B silicon wafer, the specific implementation operation is as follows: place the diluted liquid in a water bath and heat it to the experimental temperature, then place the experimental piece - lightly doped silicon wafer in the liquid for 24 hours, compare the change in the weight of the experimental piece before and after the experiment, and the static corrosion results are shown in Table 2.

[0066] Example 4

[0067] Prepare 5L of silicon edge polishing liquid:

[0068] According to the weight percentage, 0.18 parts of potassium hydroxide, 4 parts of hexamethylammonium hydroxide, 0.04 parts of tartaric acid, and 0.06 parts of fatty acid polyoxyethylene ester are dissolved in 23 parts of DIW to prepare a premix; then the premix is ​​added to 4159g (72 parts) of colloidal silicon dioxide with a particle size of 80nm and a concentration of 40% under stirring to obtain No. 4 edge polishing liquid, whose pH is about 11.

[0069] First, take the prepared No. 4 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 1, and the results under the silicon wafer edge microscope are shown in Figure 4 .

[0070] Secondly, take the above-configured No. 4 edge polishing liquid and conduct a static corrosion experiment with a liquid dilution ratio of 1:15; the experimental temperature is 30°C, the experimental time is 24 hours, the experimental object: lightly doped B silicon wafer, the specific implementation operation is as follows: place the diluted liquid in a water bath and heat it to the experimental temperature, then place the experimental wafer - lightly doped silicon wafer in the liquid for 24 hours, compare the change in the weight of the experimental wafer before and after the experiment, and the static corrosion results are shown in Table 2.

[0071] Table 1

[0072]

[0073] Table 2

[0074] Example 1 Example 2 Example 3 Example 4 Static corrosion (mg) 135.8 147.6 71.2 68.9

[0075] By comparing Examples 1-2 and 3-4, it can be seen that by using silica sols with particle sizes of 60nm and 80nm, respectively, the smaller the particle size, the higher the removal rate and the smoother and more contaminant-free edge profile and the lower edge surface roughness can be obtained, thereby achieving rate optimization and surface roughness optimization. Therefore, in order to obtain better edge surface roughness and faster removal rate, in the selection of silica sol, silica sol with a small particle size can be preferred to silica sol with a large particle size.

[0076] It can be seen from Examples 1-4 that the addition of different types of rate accelerators has different effects on the removal rate of the silicon wafer. It can be seen from Table 1 that the removal rates of Examples 3 and 4 are higher than those of Examples 1 and 2, proving that the addition of tetramethylammonium hydroxide has a lower promoting effect on the removal rate of the silicon wafer than the addition of hexamethylammonium hydroxide. In other words, in order to obtain a faster removal rate, it is recommended to give priority to hexamethylammonium hydroxide.

[0077] It can be seen from Examples 1-4 that the addition of different types of surfactants has different protective effects on the edge polishing of silicon wafers. It can be seen from Table 2 that the static corrosion values ​​of Examples 3 and 4 are lower than those of Examples 1 and 2, which means that the protective effect of fatty acid polyoxyethylene esters on silicon wafers is better than that of alkylphenol polyoxyethylene ethers. Therefore, in order to achieve the risk of no chemical contamination on the edge of silicon wafers during silicon wafer processing, it is recommended to give priority to fatty acid polyoxyethylene esters.

[0078] Example 5

[0079] Prepare 5L of silicon edge polishing liquid:

[0080] According to the weight percentage, 0.58 parts of ammonia water, 0.19 parts of lactic acid, and 0.1 parts of AEO are dissolved in 19 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 80 parts of colloidal silica with a particle size of 70nm and a concentration of 30% under stirring to obtain No. 5 edge polishing liquid, whose pH is about 11.

[0081] First, take the prepared No. 5 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 3.

[0082] Example 6

[0083] Prepare 5L of silicon edge polishing liquid:

[0084] According to the weight percentage, 1.9 parts of tetramethylammonium hydroxide, 0.19 parts of lactic acid, and 0.09 parts of AEO are dissolved in 19 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 80 parts of colloidal silica with a particle size of 70nm and a concentration of 30% under stirring to obtain a No. 6 edge polishing liquid with a pH of about 11.

[0085] First, take the prepared No. 6 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 3.

[0086] Example 7

[0087] Prepare 5L of silicon edge polishing liquid:

[0088] According to the weight percentage, 0.39 parts of triethanolamine, 0.19 parts of lactic acid, and 0.1 parts of AEO are dissolved in 19 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 80 parts of colloidal silica with a particle size of 70nm and a concentration of 30% under stirring to obtain No. 7 edge polishing liquid, whose pH is about 11.

[0089] First, take the prepared No. 7 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 3.

[0090] Example 8

[0091] Prepare 5L of silicon edge polishing liquid:

[0092] According to the weight percentage, 0.29 parts of propylene diamine, 0.19 parts of lactic acid, and 0.1 parts of AEO are dissolved in 19 parts of DIW to prepare a premixed liquid; then the premixed liquid is added to 80 parts of colloidal silica with a particle size of 70nm and a concentration of 30% under stirring to obtain No. 8 edge polishing liquid, whose pH is about 11.

[0093] First, take the prepared No. 8 edge polishing liquid, use the Zhiling 1280 polishing machine, the polishing pad is: SUBA800 flat pad, the polishing pressure is: 280kg, the polishing head / disc speed is: 30 / 29rpm, the circulation flow is 3L / min. The polishing disk temperature is controlled at 30±5℃, and the liquid dilution ratio is 1:15; the results after polishing are shown in Table 3.

[0094] Table 3

[0095]

[0096] It can be seen from the rate comparison of Examples 5-8 that when propylene diamine is used as the rate accelerator, the polishing rate is optimal. Therefore, in the approach to increasing the rate, propylene diamine is preferably selected as the rate accelerator.

[0097] The removal rate in each embodiment of the present application is tested by a non-contact thickness tester, and the roughness is tested by an atomic force microscope.

[0098] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A polishing liquid for improving edge roughness, characterized in that: According to parts by weight, it includes the following components: The rate accelerator is selected from at least one of alkali metal hydroxides, alkali metal carbonates, quaternary ammonium hydroxides, and amines.

2. The polishing liquid for improving edge roughness according to claim 1, characterized in that: The rate accelerator is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, tetramethylammonium hydroxide, triethanolamine, ammonia water, benzalkonium chloride, benzalkonium bromide, bis-decyl dimethyl ammonium chloride, laurylamine dipropylene diamine, propylene diamine, quaternary ammonium oxide, alkyl dimethyl benzyl ammonium chloride, composite quaternary ammonium salt and polyquaternary ammonium salt.

3. The polishing liquid for improving edge roughness according to claim 1, characterized in that: The particle size of the sol-type silica is in the range of 30-150 nm.

4. The polishing liquid for improving edge roughness according to claim 1, characterized in that: The surfactant is selected from at least one of a nonionic surfactant, an amphoteric surfactant, and a polyol surfactant.

5. The polishing liquid for improving edge roughness according to claim 4, characterized in that: The surfactant is selected from at least one of long-chain fatty alcohol polyoxyethylene ethers, alkylphenol polyoxyethylene ethers, fatty acid polyoxyethylene esters, polyoxyethylene alkylamines, polyoxyethylene alkylamides and polyethers.

6. The polishing liquid for improving edge roughness according to claim 1, characterized in that: It also includes 0.01-1 parts of a dispersant.

7. The polishing liquid for improving edge roughness according to claim 6, characterized in that: The dispersant is an inorganic electrolyte dispersant; the inorganic electrolyte dispersant is selected from at least one of phosphates, silicates and carbonates.

8. The polishing liquid for improving edge roughness according to claim 1, characterized in that: The pH adjuster is an organic acid.

9. The polishing liquid for improving edge roughness according to claim 8, characterized in that: The pH regulator is selected from at least one of formic acid, acetic acid, propionic acid, citric acid, oxalic acid, tartaric acid, malic acid, lactic acid, nitrilotriacetate amine, sodium nitrilotriacetate, ethylenediaminetetraacetic acid, and sodium ethylenediaminetetraacetate.

10. The polishing liquid for improving edge roughness according to any one of claims 1 to 9, characterized in that: The pH value of the polishing liquid for improving edge roughness is in the range of 9-12.